THE PROBLEMS OF MODELING OF SOCIO-ECONOMIC SYSTEM OF RESORT AND RECREATION COMPLEX - Vladimir Vladimirovich Mishin; Eduard Grigorievich Yanukian; Irina Vladislavovna Mantorova (Современная наука и инновации, 2022)
The article considers particular aspects of the modeling of socio-economic system of the resort and recreational complex (RRC). The authors analyze RRC properties, which must be considered in the selection process and the model building. The authors offer a model of socio-economic complex of RRC on PLS-PM methodology, taking into account the selected peculiarities of the RRC.